Evaluation of the Role of Public Accountants on the Application of Know your Customer Principle to Assess Client Risk in Preventing Money Laundering (Case Study on Public Accounting Firm in Yogyakarta Area) - Salsabila Nur Aini Sekarningrum (Indonesian Journal of Business Analytics, 2025)
The purpose of this study is to describe the implementation and strategy of PMPJ implementation by Public Accountants (KAP) in the Yogyakarta region. In addition, this study also aims to understand the role of public accountants in the Yogyakarta region related to the implementation of PMPJ to assess client risk in preventing money laundering. This study uses a qualitative descriptive research method with a case study approach. There are two types of data sources used in this study: primary data obtained through in-depth interviews with KAPs in the Yogyakarta region using convenience sampling techniques and secondary data obtained through data related to PMPJ policies. The findings of this study, informants from four KAPs in the Yogyakarta region have implemented PMPJ in accordance with regulatory guidelines, namely SE Number 7/PPPK/2019. The role of public accountants in efforts to prevent money laundering is still necessary. In addition, auditing financial statements is also an obligation for companies and a form of professionalism of public accountants based on the principles of the profession, namely the embodiment of integrity and compliance with regulations.